THE STRATEGIC ROLE OF KNOWLEDGE MANAGEMENT IN ACHIEVING ORGANIZATIONAL EXCELLENCE THROUGH DIGITAL SKILLS (American Journal of Research in Humanities and Social Sciences, 2024)
The study aimed to reveal the strategic role of knowledge management in achieving organizational excellence through digital skills. For the purpose of achieving the objectives of the study, the deductive analytical approach was used to analyze the information and obtain accurate results. In order to ensure the existence of a relationship between the study variables, a questionnaire tool was used to collect information about the study variables and their dimensions, and they were analyzed through a set of statistical tools and methods provided by the statistical software package ( SPSS, SMART PLS, AMOS). Asiacell Communications Company was selected as a population for the current study, and the sample consisted of (341) employees.The most prominent results of the study were the existence of an influence and connection to the strategic role of knowledge management in achieving organizational excellence through the mediation of digital skills. Among the most prominent recommendations of the study is to revitalize and activate the knowledge management strategy by working on the academic rooting of knowledge performance and placing it within the organizational structure independently.